2021
DOI: 10.7759/cureus.18137
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in COVID-19 Patients in Southern California – Retrospective Multicenter Study

Abstract: The majority of patients infected with coronavirus disease 2019 (COVID-19) recover from the illness after suffering mild to moderate symptoms, while approximately 20% progress to severe or critical disease, which may result in death. Understanding the predictors of severe disease and mortality in COVID-19 patients will help to risk stratify patients and improve clinical decision making. US data to inform this understanding are, however, scarce. We studied predictors of COVID-19 mortality in a cohort of 1,116 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…CRP was predictive of mortality in both the young and elderly in our study [6]. High CRP levels have been noted in COVID-19 patients and have been associated with severe COVID-19, the need for ICU-level care [7], and in-hospital mortality [4,8,9]. However, our study found no differences in hospital length of stay, ICU admission, and ventilator use between the two age groups.…”
Section: Discussioncontrasting
confidence: 45%
“…CRP was predictive of mortality in both the young and elderly in our study [6]. High CRP levels have been noted in COVID-19 patients and have been associated with severe COVID-19, the need for ICU-level care [7], and in-hospital mortality [4,8,9]. However, our study found no differences in hospital length of stay, ICU admission, and ventilator use between the two age groups.…”
Section: Discussioncontrasting
confidence: 45%